Effect of light, temperature and diet on the fatty acid profile of the tropical sea anemone Aiptasia pallida. (24th January 2013) - Leal, M.C.; Nunes, C.; Kempf, S.; Reis, A.; da Silva, T.L.; Serôdio, J.; Cleary, D.F.R.; Calado, R.
Abstract: Sea anemones of the genus Aiptasia are used as biological models for research and as a prey for the culture of the highly priced ornamental nudibranch Aeolidiella stephanieae . Symbiotic Aiptasia display a remarkable trophic plasticity, being able to fulfil their energetic demands heterotrophically and autotrophically. Consequently, they display a highly variable fatty acid (FA) profile. The objective of the present study was to analyse how light regime (12 h light : 12 h dark versus 24 h darkness), water temperature (22 versus 26 °C) and diet ( Artemia nauplii versus enriched Artemia metanauplii) affect the FA composition of A. pallida . The FA profile of wild specimens was also analysed. The dominant FAs of cultured A. pallida were 16:0, 18:1 n ‐9 and 22:6 n ‐3. Higher FA levels were recorded when anemones were exposed to light, with this factor explaining the largest amount of variation in the composition of FA profiles. Cultured A. pallida that best mimicked wild anemones were obtained when using a regular light regime, Artemia metanauplii and 22 °C water temperature. Higher FA levels were obtained at a higher temperature and by providing nauplii to cultured anemones. The present study also indicated that A. pallida has the potential to recycle nutrients in marine aquacultures.